APPLICATION OF PEER ASSESSMENT TO IMPROVE MASTERY OF PROCEDURAL KNOWLEDGE IN ACCOUNTING LEARNING SERVICE COMPANIES - Nor, Baseran; Suratno, Suratno; Harahap, Alfi Fadhilah Hakim; Rizky, Maulana; Saputri, Lydia; Arifah, Nining (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2024)
This study aims to evaluate the effectiveness of peer assessment in increasing students' mastery of procedural knowledge in service company accounting learning. Procedural knowledge is essential in accounting because it includes applying accounting concepts and theories in real-world contexts, such as recording transactions and preparing financial statements. The peer assessment method allows students to assess their classmates' work, provide constructive feedback, and improve their understanding through the evaluation process. This study uses a descriptive method with a quantitative approach. The research subjects are 55 4th-semester students in the Accounting of Service Companies lecture in the Economics Education Study Program, FKIP ULM, who study accounting for service companies. Data was collected through observation of the learning process and questionnaires given to students after applying the peer assessment method. This questionnaire evaluates students' increased understanding of service company accounting procedures and their attitudes toward using peer assessment in learning. The results of the study show that the application of peer assessment has a positive effect on the mastery of procedural knowledge. Most students feel that this method helps them better understand the steps in compiling the financial statements of service companies. In addition, students feel more confident and motivated to learn after receiving feedback from their peers. Thus, peer assessment effectively increases the mastery of procedural knowledge in service company accounting learning.